Pernikahan sebagai Instrumen Kekuasaan dan Status Sosial: Studi Historis tentang Praktik Perkawinan di Kalangan Ménak Sunda - Pujo Pangestu; Asmawi Asmawi; Ahmad Muhtadi Anshor (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This study aims to analyze marriage practices among the Sundanese aristocracy (ménak) during the pre-independence period of Indonesia, focusing on their relationship to social status, power, and wealth. The research explores socio-economic motivations underlying marriage practices that often transcended love or religious devotion, functioning instead as instruments for consolidating authority and sustaining elite lineage. The study employs a library research method with content and descriptive analysis approaches. Data were collected from historical literature, customary law sources, and anthropological studies, and were validated through corroboration analysis by comparing data across multiple references. The findings reveal that marriages among the Sundanese nobles served as strategic tools for preserving noble bloodlines, strengthening political alliances, and maintaining family power and economic stability. Practices such as early arranged marriages, polygamy, and politically motivated unions were integral to this socio-cultural system. Culturally, marriage symbolized honor and the legitimization of social hierarchy within traditional Sundanese society. The study recommends further research on the evolution of marriage values and practices among contemporary Sundanese communities within the framework of modernity and gender.